Gaya Bahasa dalam Konten Tiktok Vilmei pada Fenomena Viral Pemblokiran dan Pemulihan Tiktokshop - Desma Yuliadi Saputra; Rina Andriani (Morfologi : Jurnal Ilmu Pendidikan, Bahasa, Sastra dan Budaya, 2026)
Social media has become a primary platform for information dissemination and public opinion formation, making language use a crucial factor in shaping audience perceptions. One phenomenon that attracted widespread public attention was the viral blocking and subsequent restoration of Vilmei's TikTok account, which generated various forms of communication directed toward her followers. The uploaded content served not only as a means of communication but also demonstrated the use of figurative language capable of evoking emotions, fostering empathy, and encouraging audience engagement. This study aims to describe the types of figurative language employed in Vilmei's TikTok content and explain their functions in constructing meaning and influencing public responses. The study adopted a descriptive qualitative approach using stylistic analysis. The data consisted of utterances and textual content found in Vilmei's TikTok videos uploaded during the account blocking and restoration period. Data were collected through documentation, observation, and note-taking techniques, while data analysis followed the Miles and Huberman model. The findings reveal that the dominant language styles include metaphor, repetition, hyperbole, and emotive diction, which function to strengthen emotional expression, build emotional closeness with followers, enhance audience engagement, shape the creator's self-image, and influence public responses. This study demonstrates that language style plays an essential role in creating effective communication on social media and can serve as a reference for language studies and digital literacy.